Omissions, conflations, and false dichotomies: Conceptual and empirical problems with the Barbey & Sloman account. - Brase, Gary L. (My University, 2007)
Both the theoretical frameworks that organize the first part of Barbey & Sloman's (B&S's) target article and the empirical evidence marshaled in the second part are marked by distinctions that should not exist (i.e., false dichotomies), conflations where distinctions should be made, and selective omissions of empirical results - within the very studies discussed - that create illusions of theoretical and empirical favor.
Keywords: Bayesian reasoning; Frequencies